Green and Sustainable Concrete – The Potential Utilization of Rice Husk Ash and Egg Shells - Ashfaque Ahmed Jhatial; Wan Inn Goh; Kim Hung Mo; Samiullah Sohu; Imtiaz Ali Bhatti (Salehan Institute of Higher Education, 2019)
Concrete which is widely used material in the construction industry, has a carbon footprint. Approximately 10% of global Carbon Dioxide (CO2) gas is emitted during the production of cement which is vital ingredient of concrete. The increase in production of cement affects global warming and climate change. Therefore, many have attempts have been made to develop green and sustainable concrete by utilizing different waste materials. With the utilization of waste materials as cement replacement, the CO2 gas emissions can be reduced as well as resolve the environmental issues that the inhabitants face during the disposal of such waste materials. This paper reviews the potential and innovative utilization of Rice Husk Ash (RHA) and Eggshells as partial cement replacement to develop green concrete. RHA which is rich in silica and eggshells contain identical amount of calcium oxide as cement, when finely grinded and used together as partial cement replacement, can trigger a pozzolanic reaction, in which silica reacts with calcium oxide resulting in the formation of calcium silicates which are responsible for achieving higher strengths.